Identifikasi Etika Bisnis Islam dalam Jual Beli Online dengan Sistem Reseller - Nur Afifah (Jurnal Riset Ilmu Ekonomi dan Bisnis, 2022)
Abstract. In this era, many technological developments that can be utilized by sellers, such as online sales transactions. Business actors need to be reviewed and analyzed in the practice of buying and selling online with the reseller system is correct and the application of Islamic Business Ethics in buying and selling online with the reseller system in Indonesia has been implemented properly and correctly. In this study, the data was collected through questionnaires distributed to 10 people where respondents had been involved in the online reseller sales system. The results of the questionnaire responses will be collected to be observed and analyzed in more detail and depth. The results of this study showed that, from 10 informants selling and buying online with reseller system at least there are still those who have not applied Islamic Business Ethics. This is seen from the explanation of the store's operating hours and delivery of goods, responsibility for the products sold and complaints from consumers, and being honest in selling does not display images that are not from the product itself. Business actors must understand, understand and apply Islamic Business Ethics in order to create a sense of justice and protected consumer rights in conducting online buying and selling transactions. Islamic business ethics includes four aspects, honest and trustworthy, discipline, responsibility and gratitude. Abstrak. Pada era ini, banyak perkembang teknologi yang bisa dimanfaatkan oleh penjual, seperti transaksi penjualan secara online. Pelaku usaha perlu ditinjau dan dianalisa dalam praktik jual-beli online dengan sistem reseller sudah benar dan penerapan etika bisnis Islam dalam jual-beli online dengan sistem reseller di Indonesia sudah diterapkan dengan baik dan benar. Dalam penelitian ini, data dikumpulkan melalui kuisioner yang disebarkan ke 10 orang dimana responden pernah terjun dalam sistem penjualan reseller online. Hasil dari tanggapan kuisioner ini akan dikumpulkan untuk diobservasi dan dianalisa secara lebih detail dan mendalam. Hasil dari penelitian ini menunjukkan bahwa, dari 10 informan jual beli online dengan sistem reseller sedikitnya masih ada yang belum menerapkan etika bisnis Islam. Hal ini dilihat dari penjelasan jam operasional toko dan pengiriman barang, tanggung jawab atas produk yang dijual dan komplain dari konsumen, dan jujur dalam berjualan tidak menampilkan gambar yang bukan dari produk sendiri. Para pelaku usaha harus mengerti, memahami dan menerapkan etika bisnis Islam agar terciptanya rasa keadilan dan terlindunginya hak konsumen dalam melakukan transaksi jual beli online. Etika bisnis Islam meliputi empat aspek, jujur dan amanah, disiplin, bertanggung jawab dan syukur.